Integrasi Pendidikan Hukum Islam dalam Pembentukan Karakter Anti-Bullying pada Siswa Madrasah Aliyah Miftahussalam Medan - Sakban Lubis; Hadi Saputra Panggabean; Tumiran Tumiran; Ismail Mukhtar Nasution (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study examines the integration of Islamic legal education in shaping anti-bullying character among students at Madrasah Aliyah Miftahussalam Medan. The research is grounded in the growing concern over the rise of bullying in educational environments, which disrupts students’ psychological well-being, learning processes, and school order. The central research question explores how Islamic legal principles—emphasizing justice, responsibility, brotherhood, and the prohibition of wrongdoing—can be systematically embedded to cultivate students’ capacity to prevent and resist bullying. Using a qualitative design, data were collected through interviews, observations, and document analysis, and subsequently analyzed through data reduction, data display, and conclusion drawing. The findings reveal that Islamic legal education is integrated through the strengthening of fiqh muamalah and ethics materials, along with the internalization of Sharia-based values in extracurricular activities and school culture. Routine habituation of respectful conduct, teacher role-modeling, and Sharia-oriented disciplinary enforcement effectively foster empathy, responsibility, and mutual respect among students. These efforts contribute to a noticeable decline in bullying incidents and enhance students’ awareness of maintaining social harmony. The study concludes that Islamic legal education plays a significant role in developing anti-bullying character and that a systematic, holistic integration of Islamic legal values provides an effective model for creating a safe, humanistic, and civilized educational environment.